2007
DOI: 10.1038/sj.cdd.4402257
|View full text |Cite
|
Sign up to set email alerts
|

R-Roscovitine simultaneously targets both the p53 and NF-κB pathways and causes potentiation of apoptosis: implications in cancer therapy

Abstract: Seliciclib (CYC202, R-Roscovitine) is a 2, 6, 9-substituted purine analog that is currently in phase II clinical trials as an anticancer agent. We show in this study that R-Roscovitine can downregulate nuclear factor-kappa B (NF-jB) activation in response to tumor necrosis factor (TNF)a and interleukin 1. Activation of p53-dependent transcription is not compromised when RRoscovitine is combined with TNFa. We characterize the molecular mechanism governing NF-jB repression and show that RRoscovitine inhibits the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(59 citation statements)
references
References 40 publications
4
53
0
2
Order By: Relevance
“…R-roscovitine is known to promote apoptosis in cancer cell lines by inhibition of RNA polymerase-II leading to down-regulation of the key survival protein Mcl-1 [24]. It has also been suggested that NF-kB activation at the level of IkB kinase kinase activity is inhibited by R-roscovitine [25]. Given that both Mcl-1 and NF-kB are key components of neutrophil survival regulation we were keen to address the hypothesis that R-roscovitine might act via similar mechanisms in the inflammatory neutrophil.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…R-roscovitine is known to promote apoptosis in cancer cell lines by inhibition of RNA polymerase-II leading to down-regulation of the key survival protein Mcl-1 [24]. It has also been suggested that NF-kB activation at the level of IkB kinase kinase activity is inhibited by R-roscovitine [25]. Given that both Mcl-1 and NF-kB are key components of neutrophil survival regulation we were keen to address the hypothesis that R-roscovitine might act via similar mechanisms in the inflammatory neutrophil.…”
Section: Discussionmentioning
confidence: 99%
“…R-roscovitine has been investigated previously from an anticancer perspective and has been found to promote apoptosis in myeloma cell-lines by down-regulation of Mcl-1 [24]; indeed R-roscovitine and other CDK inhibitors are undergoing Phase I and II clinical trials for the treatment of various types of cancers. Recently, it was shown that R-roscovitine could directly inhibit NF-kB at late time-points in cancer cell-lines [25], a finding that, if applicable to neutrophils, might provide insight into the antiinflammatory properties of R-roscovitine. In this paper we show that R-roscovitine can overcome powerful pro-survival signals to promote neutrophil apoptosis, without directly affecting activation status or key signalling pathways, but by down-regulating the important pro-survival protein Mcl-1 at the level of transcription.…”
Section: Introductionmentioning
confidence: 99%
“…The phosphorylation levels of these two sites are dramatically increased upon stimulation of NF-kB activity. 29,30 Moreover, studies show that tumor cell apoptosis induced by anticancer reagents is associated with decreased p65 phosphorylation at Ser536 residue, [31][32][33] suggesting that p65 Ser536 phosphorylation is important for maintaining cancer cell survival and can be inhibited by anticancer reagents. In this study we showed that not only phosphorylation of Ser536 but also phosphorylation of Ser468 is downregulated during HDAC inhibitor-induced apoptosis of EC cells.…”
Section: Discussionmentioning
confidence: 99%
“…In vivo activity in mice bearing colorectal carcinoma xenografts, but also in hematopoietic progenitors (Mcclue et al, 2002;Raynaud et al, 2005;Song et al, 2007) and enhancement of antitumor effects of radiation and doxorubicin in combination with Rroscovitine was reported (Appleyard et al, 2009;Maggiorella et al, 2003). Like flavopiridol and other Cdk inhibitors with broad spectrum, several additional effects have been described for R-roscovitine in vitro: interruption of transcriptional elongation, interference with survival-associated pathways (IB kinase inhibition), induction of p53 phosphorylation and apoptosis (Alvi et al, 2005;Dey et al, 2008;Hahntow et al, 2004). A novel potent Cdk inhibitor with striking similarity to R-roscovitine regarding both chemical structure and cytotoxic properties is pyrazolo[1,5-a]pyrimidine derivative SCH 727965 (Parry et al, 2010).…”
Section: Overview Of Small Molecule Cdk Inhibitors: Selectivity and Mmentioning
confidence: 99%